Fundamentals of urine and body fluid analysis - Brunzel, Nancy A. (St. Louis, Missouri : Elsevier, Saunders, 2013)
Renowned for its clear writing style, logical organization, level and depth of content, and excellent color illustrations, 3rd Edition covers the collection and analysis of urine, fecal specimens, vaginal secretions, and other body fluids such as cerebrospinal, synovial, seminal, amniotic, pleural, pericardial, and peritoneal fluids. Expert author Nancy Brunzel shares her extensive knowledge and expertise in the field, presenting key information and essential techniques and procedures, as well as easy-to-grasp explanations of how to correlate data with basic anatomy and physiology to understand pathological processes. NEW! Automation of Urine and Body Fluid Analysis chapter helps you understand the automated procedures being used in more and more labs. NEW! Body Fluid Analysis: Manual Hemacytometer Counts and Differential Slide Preparation chapter ensures you know how to perform manual analysis methods. UPDATED! Coverage of the latest instrumentation keeps you up to date with the technology used in today's laboratories.
Microscopy -- Quality assurance and safety -- Urine specimen types, collection, and preservation -- The kidney -- Renal function -- Physical examination of urine -- Chemical examination of urine -- Microscopic examination of urine sediment : urine sediment image gallery -- Renal and metabolic disease -- Fecal analysis -- Seminal fluid analysis -- Amniotic fluid analysis -- Cerebrospinal fluid analysis -- Synovial fluid analysis -- Pleural, pericardial, and peritoneal fluid analysis -- Vaginal fluid analysis -- Automation of urine and body fluid analysis -- Body fluid analysis : manual hemacytometer counts and differential slide preparation.
Includes bibliographical references and index.
Keywords: URINE -- ANALYSIS